Implementasi Pendidikan Karakter Melalui Pembelajaran PJOK di Kelas 5 SDN 1 Giri Madya - Muhamad Supriadi; Nur Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
The research objective in this study was to find out how to implement character education through PJOK learning in grade 5 SDN 1 Giri Madya. The approach used in this research is a qualitative approach with a descriptive research type. The data source in this study is the teacher. The teacher in question is a PJOK teacher who teaches in grade 5 at SDN 1 Giri Madya. Data collection procedures used using the method of observation and interviews. Then using data analysis techniques in the form of data reduction, data presentation, and drawing conclusions. The results of this study are that the implementation of character education through PJOK learning in grade 5 of SDN 1 Giri Madya has been implemented by using the parable and habituation method. This parable method means that the teacher will give examples of real things to students so that students are easy to understand. Likewise with the teacher's habituation method to familiarize students with honest, responsible, cooperative and never give up behavior